Ang tangi kong pag-ibig - Torres, Mar S.; Conde, Camacho; Galaura, Fausto J.; Vera, Jose O. (Sampaguita Pictures, 1955)
Jovita (Carmen Rosales) seems to have it all: a successful career as a bar singer, a glamorous life in the city, and a rich lover? but at a price. Rumors attacking her dignity and personal life hound her, and not being able to take them lightly, she runs back to the province and rejoins her father and sister. There, she starts a new life and falls in love again, this time with Sergio (Rogelio De La Rosa), a young man belonging to a well-off family. Things seem fine until her ex-lover appears and stirs things up for Jovita, prompting her to flee once more ? this time into the accepting arms of a convent. Left hanging in the air, Sergio looks for his only love while Jovita turns a blind eye to her past. How will they find each again? Fate and the strength of their love will show them the way.